Long-term results after endoscopic drainage of pancreatic pseudocysts: a single-center experience - Rückert, Felix; Lietzmann, Anja; Wilhelm, Torsten; Sold, Moritz; Kähler, Georg; Schneider, Alexander (Pancreatology, 2017)
Background: Pancreatic pseudocysts (PPC) are collections of fluid encapsulated within a well-defined inflammatory wall that develop during pancreatic inflammation. Internal drainage represents the standard of care in lesions that persist and lead to symptoms and complications. Only limited data are available on long-term results and recurrence of PPC after drainage procedures. Thus, the aim of the present study was to analyse the long-term outcome after endoscopic drainage of PPC. Material and methods: Patient data were retrospectively collected by review of clinical records of the University Medical Center Mannheim. We assessed the clinical short-term outcome (results in the first 30 days after initial drainage procedure), medium-term outcome (results 6 months after initial drainage procedure) and long-term outcome (results after stent removal). We performed statistical analysis to identify possible risk factors for recurrence of PPC. Results: We identified 51 patients with initially successful endoscopic drainage of the PPC (n = 51/53, 96%). Among this cohort, 43 patients were available for assessment of medium-term results. In 82.9% of these 43 patients the drainage could be removed after successful treatment of the PPC. Thirty patients were available for long term follow-up with a mean observation period of 42.2 months (SD 32.8 months). Among these patients, seven (n = 7/30, 23.3%) had recurrent PPC. Approximately half of the recurrent cysts arose in different anatomical regions and most patients with recurrence had chronic pancreatitis. Conclusion: Endoscopic drainage represents an effective treatment for PPC. Approximately one quarter of the patients developed recurrent PPC. Half of recurrent PPC developed in different pancreatic regions than the initial PPC.
Gesehen am 18.06.2018
Available online 3 June 2017